Integration of phenomenon-based and play-based learning in primary science - Prapatchit Techa; Sakda Swathanan; Wichaya Pewkam; Natad Assapaporn (International Journal of Evaluation and Research in Education (IJERE), 2026)
Primary school students in Thailand continue to struggle with science process skills and creative thinking, a challenge underscored by Thailand’s lowest Programme for International Student Assessment (PISA) science scores in 20 years. Traditional instruction emphasizing content memorization while neglecting real-world application has been identified as a major contributing factor. Addressing this issue is critical, as both competencies are foundational for 21st-century learning. This study examined the effects of an integrated phenomenon-based learning and play-based learning (PhBL-PBL) innovation on Grade 2 students’ science process skills and creative thinking skills. A one-group posttest-only design was adopted with 41 students in an authentic Thai primary classroom. Data were collected using validated instruments and analyzed through descriptive statistics and one-sample t-tests against predefined performance criteria. Results showed that 92.68% of students achieved creative thinking skills at a good level or above, and 85.37% reached the same threshold for science process skills, with mean scores for both domains significantly exceeding the criterion level (p